An underwater self-anchoring and hierarchical sequence-structured organic-inorganic hybrid repair material, and preparation and application thereof
Patent Information
- Application Number
- CN202611250670.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]本发明的目的在于提供一种水下自锚固及分阶序构固化的有机-无机杂化修复材料,以解决或缓解上述现有技术中存在的水下初始黏附力差、易受水流冲刷脱落以及无法在富水环境中稳定固化构建结构强度的问题
本发明的有机-无机杂化修复材料中,通过采用低粘度(4000-6000mPa·s)的端羟基聚二甲基硅氧烷为基质,并摒弃常规的高活性硅酮交联体系,打破了传统材料的内聚力制约黏附力的技术限制。挤出施胶瞬间,材料呈现高浸润凝胶状态,协同液态丁基橡胶与氢化松香甘油酯构成的强效疏水增粘相,能够强制排开混凝土表面的游离水膜,使材料深入缝隙并渗入微观孔隙,表现出优异的物理润湿。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of marine engineering and infrastructure repair materials, and relates to an underwater self-anchoring and step-by-step curing organic-inorganic hybrid repair material and its preparation and application, specifically applied to the direct bonding repair of concrete structures such as underwater bridge piers, wharves, and deep-water pipelines. Background Technology
[0002] Underwater concrete structures such as cross-sea bridges, docks, tunnels, and dams are subjected to extremely harsh environments, including abundant water, strong water flow, and chloride ion corrosion, making them highly susceptible to defects such as cracks, spalling, and erosion voids. Traditional underwater repair materials, such as underwater epoxy resins and rapid-hardening cement-based grouting materials, suffer from poor underwater interface wettability, severe moisture interference during curing, and insufficient initial erosion resistance. They are easily washed away and detached in strong water flow environments, making long-term in-situ repair difficult.
[0003] In recent years, although organic-inorganic hybrid materials have been introduced into underwater repair due to their combination of the flexibility of polymer materials and the strength of inorganic materials, conventional high-viscosity silicone rubber systems or polyurethane systems exhibit extremely poor interfacial rheology before complete curing. More seriously, existing repair materials often fail to balance the contradiction between "material cohesion" and "interfacial adhesion": the introduction of highly cross-linked systems in pursuit of rapid curing and high strength results in materials that behave like "high-toughness putty" underwater. This high cohesion also hinders the material's ability to wet the micropores of concrete, preventing effective drainage of the water film on the substrate surface and leading to underwater adhesion failure.
[0004] Therefore, developing an organic-inorganic hybrid repair material that breaks with conventional thinking, achieves interfacial wetting and self-anchoring by reducing initial cohesion, and can resist water erosion and achieve phased curing in underwater environments is of great significance for promoting the development of underwater concrete repair technology. Therefore, an improved technical solution is needed to address the shortcomings of the existing technologies. Summary of the Invention
[0005] The purpose of this invention is to provide an organic-inorganic hybrid repair material that is self-anchored and undergoes phased curing underwater, in order to solve or alleviate the problems of poor initial underwater adhesion, susceptibility to water erosion and detachment, and inability to stably cure and build structural strength in water-rich environments that exist in the prior art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: An underwater self-anchoring and stepwise curing organic-inorganic hybrid repair material, comprising the following components by mass parts: The composition includes: 100 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 4000-6000 mPa·s, 5-15 parts of hydrophobic tackifying resin, 1-5 parts of thixotropic agent, 15-30 parts of inorganic powder filler, 15-30 parts of liquid butyl rubber, 15-30 parts of sulfoaluminate cement, 2-5 parts of long-chain alkylsilane, 1-4 parts of delayed crosslinking agent, 1-3 parts of silane coupling agent, 0.05-0.15 parts of catalyst, 1-4 parts of tannic acid, and 1-4 parts of short-cut reinforcing fibers with a length of 1-3 mm.
[0007] Preferably, the hydrophobic tackifying resin is one of hydrogenated rosin glycerol ester, hydrogenated rosin pentaerythritol ester, or polymerized rosin; the thixotropic agent is a mixture of polyamide wax and hydrophobic fumed silica in a mass ratio of (1.5~2):1 or is only polyamide wax; the chopped reinforcing fiber is one of chopped basalt fiber, alkali-resistant glass fiber, or carbon fiber.
[0008] Preferably, the inorganic powder filler is a mixture of nano-calcium carbonate and microsilica in a mass ratio of (2~2.57):1, or is only nano-calcium carbonate; the sulfoaluminate cement is grade 42.5 sulfoaluminate cement or grade 52.5 sulfoaluminate cement.
[0009] Preferably, the long-chain alkylsilane is hexadecyltrimethoxysilane or octadecyltriethoxysilane; the delayed crosslinking agent is one of tetraethyl orthosilicate, methyltriethoxysilane or phenyltrimethoxysilane; the silane coupling agent is KH-560, or a mixture of KH-792 and KH-560 in equal proportions; and the catalyst is dibutyltin dilaurate.
[0010] The above-mentioned organic-inorganic hybrid repair material has an initial underwater contact angle of no more than 22°, a vertical anti-sagging height of no less than 120 mm, and an underwater bonding strength of no less than 2.6 MPa.
[0011] The above-mentioned method for preparing organic-inorganic hybrid repair materials involves the following steps in a planetary stirred tank equipped with a jacketed temperature control and vacuum system: Step 1: Pre-melt the hydroxyl-terminated polydimethylsiloxane, hydrophobic tackifying resin, polyamide wax and chopped reinforcing fibers at 110-120℃ and stir to activate for 15-30 minutes; Step 2: Add inorganic powder filler in batches, and add the hydrophobic fumed silica when the thixotropic agent contains hydrophobic fumed silica. Dehydrate under vacuum conditions at 110-120℃ for 40-60 minutes, and then cool down to below 40℃. Step 3: Remove the vacuum and introduce nitrogen protection. Add liquid butyl rubber and pre-dried sulfoaluminate cement at a temperature below 40°C. Then, slowly add a mixture of long-chain alkylsilane, delayed crosslinking agent, silane coupling agent and catalyst. Under high-speed shear, complete the in-situ coating of the cement surface. Step 4: Add pre-dehydrated tannic acid at a temperature below 35°C and under nitrogen protection, stir at low speed until uniform, degas under vacuum, and then seal and package.
[0012] As a pretreatment process, in step 3, the sulfoaluminate cement is pre-dried to constant weight at 110°C.
[0013] Preferably, in step 3, the high-speed shearing speed is 8000-12000 rpm, the shearing time is 15-30 minutes, and the system temperature is controlled to not exceed 45℃.
[0014] As a pretreatment process, in step 4, the tannic acid needs to be pre-dehydrated in a vacuum drying oven at room temperature for more than 24 hours.
[0015] The above-mentioned organic-inorganic hybrid repair materials are applied to underwater concrete repair by scraping, extrusion or grouting. The construction environment is underwater with a water temperature of 5-35℃. The material is wetted and anchored on the surface of damp or water-rich concrete by its own weight or construction pressure.
[0016] The beneficial effects of this invention are: In the organic-inorganic hybrid repair material of this invention, by using low-viscosity (4000-6000 mPa·s) hydroxyl-terminated polydimethylsiloxane as the matrix and abandoning the conventional high-activity silicone crosslinking system, the technical limitation of the cohesive force restricting the adhesion of traditional materials is broken. At the moment of extrusion and application, the material exhibits a highly wettable gel state. Together with the strong hydrophobic tackifying phase composed of liquid butyl rubber and hydrogenated rosin glycerol ester, it can forcibly displace the free water film on the concrete surface, allowing the material to penetrate deep into the cracks and micropores, exhibiting excellent physical wetting.
[0017] The repair material of this invention innovatively incorporates tannic acid biomimetic adhesive groups and a special silane coupling agent. Under good interfacial wetting conditions, the tannic acid polyphenol hydroxyl groups rapidly migrate to the material-concrete interface, reacting with calcium ions (Ca) on the underwater concrete surface. 2+ It forms strong coordination bonds and hydrogen bonds; combined with the covalent bond locking of epoxy / aminosilane coupling agents, it achieves rapid underwater chemical self-anchoring, solving the problem of the material being difficult to anchor under water flow in the early stage.
[0018] The core of the organic-inorganic hybrid repair material of this invention lies in achieving stepwise structural solidification in a water-rich environment. Specifically, long-chain alkylsilanes in situ encapsulate sulfoaluminate cement particles under high-speed shearing, forming "hydrophobic microcapsules" that delay their early hydration rate. Once the material is anchored underwater, as water gradually penetrates, a slow-acting crosslinking agent (such as tetraethyl orthosilicate) is first slowly triggered, forming a flexible, de-alcoholized crosslinked organic waterproof network on the surface. Subsequently, water breaks through the hydrophobic membrane, and the internal inorganic hydration phases (sulfoaluminate cement and silica fume) begin a hydration reaction to generate dense ettringite needle-like crystals and CSH gel, which interweave and overlap within the soft organic substrate, constructing a rigid support framework. This precisely transforms the originally extremely loose fluid into a high-strength, high-toughness organic-inorganic interpenetrating network structure.
[0019] The organic-inorganic hybrid repair material of this invention exhibits excellent performance. Addressing the issue of easy sagging in low-viscosity systems, it incorporates short-cut reinforcing fibers as physical "micro-reinforcing bars" to construct a flexible yet intelligent thixotropic network with polyamide wax. When applied with force, the network disintegrates smoothly to drain water; upon removal, it instantly reassembles to resist water erosion, greatly improving ease of application. This material demonstrates strong adaptability to complex underwater morphologies and vibration conditions. The repair layer exhibits high density and strong resistance to chloride ion corrosion, making it particularly suitable for rapid in-situ underwater repair and long-term protection of key marine facilities such as bridge piers of cross-sea bridges, deep-sea pipelines, and dams. It achieves a balance between interfacial adhesion and long-term chemical stability. Attached Figure Description
[0020] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein: Figure 1 Scanning electron microscope image (800x magnification) of the organic-inorganic hybrid repair material provided in the embodiments of the present invention.
[0021] Figure 2 Scanning electron microscope image (1000x magnification) of the organic-inorganic hybrid repair material provided in the embodiments of the present invention. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0023] This invention addresses the problems of existing underwater concrete repair materials, such as poor initial adhesion, susceptibility to water erosion and detachment, and incomplete deep curing, caused by the mutual constraint between the material's internal cohesion and interfacial adhesion. It provides an organic-inorganic hybrid repair material that is self-anchoring and undergoes phased curing underwater.
[0024] The study found that traditional underwater repair systems (such as conventional silicone rubber or polymers) often introduce highly active crosslinking agents in pursuit of rapid molding. This results in extremely high cohesive forces and yield stresses in the material before it fully adheres to the substrate. In water-rich environments, this leads to the formation of highly tough elastomers that cannot effectively dissipate the free water film on the concrete surface and wet the micropores. A breakthrough could be made by proactively reducing the material's cohesive forces in the initial stages, utilizing an ultra-low viscosity substrate in conjunction with a highly effective hydrophobic adhesive phase to achieve forced drainage and biomimetic anchoring at the underwater interface. Subsequently, by leveraging the difference in rates between slow organic crosslinking and microencapsulated inorganic hydration, a phased solidification process could be achieved within the material, thus solving the problems of underwater repair materials failing to adhere and maintain stability.
[0025] The underwater self-anchoring and stepwise curing organic-inorganic hybrid repair material of this invention comprises the following components in parts by mass: 100 parts of hydroxyl-terminated polydimethylsiloxane 5-15 parts of hydrophobic tackifying resin (e.g., 5, 8, 10, 12 or 15 parts). Thixotropic agent 1-5 parts (e.g., 1 part, 2 parts, 3 parts, 4 parts or 5 parts). Short-cut reinforcing fibers 1-4 parts (e.g., 1 part, 2 parts, 3 parts or 4 parts). Inorganic powder filler 15-30 parts (e.g., 15 parts, 20 parts, 25 parts or 30 parts). 15-30 parts of liquid butyl rubber (e.g., 15 parts, 20 parts, 25 parts or 30 parts). 15-30 parts of sulfoaluminate cement (e.g., 15 parts, 20 parts, 25 parts, or 30 parts). 2-5 parts of long-chain alkylsilane (e.g., 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts). 1-4 parts of a delayed crosslinking agent (e.g., 1 part, 2 parts, 3 parts or 4 parts). 1-3 parts of silane coupling agent (e.g., 1 part, 2 parts or 3 parts). Catalyst 0.05-0.15 parts (e.g., 0.05 parts, 0.1 parts, or 0.15 parts), Tannins 1-4 parts (e.g., 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts).
[0026] The aforementioned organic-inorganic hybrid repair materials abandon traditional high-viscosity (e.g., 50,000 mPa·s) base adhesives and highly active deoxime / dealcohol crosslinking agents, and innovatively use ultra-low viscosity (4,000-6,000 mPa·s) hydroxyl-terminated polydimethylsiloxane (107 adhesive) as the rheological matrix. This low-viscosity matrix endows the material with good compliance and interfacial spreading ability, enabling the material to fully conform to the uneven morphology of the concrete surface under coating action, and penetrate into the surface open pores and microcracks, providing favorable conditions for interfacial drainage and subsequent self-anchoring.
[0027] In a preferred embodiment of the organic-inorganic hybrid repair material of the present invention, the hydrophobic tackifying resin is one of hydrogenated rosin glycerol ester, hydrogenated rosin pentaerythritol ester, or polymerized rosin. Hydrogenated rosin glycerol ester is preferred as the hydrophobic tackifying resin, with liquid butyl rubber (PIB) as an auxiliary to form the hydrophobic tackifying phase. The hydrogenated rosin glycerol ester is uniformly dispersed in low-viscosity 107 adhesive through high-temperature melting, synergistically working with the extremely low water permeability liquid butyl rubber. During underwater application, this hydrophobic tackifying phase can instantly generate a strong interfacial repulsion force, forcibly displacing the water film on the concrete surface, creating a relatively dry microenvironment for subsequent chemical anchoring. If the amount of tackifying resin is too low (<5 parts), the water film dissipation capacity is insufficient; if the amount is too high (>15 parts), the paste will become too viscous, affecting the smoothness of application.
[0028] The thixotropic agent is polyamide wax and / or hydrophobic fumed silica; after high-temperature activation, the polyamide wax can construct a reversible three-dimensional hydrogen bond network in the matrix. When an external force is applied, the hydrogen bonds break, and the material rapidly liquefies and wets the substrate; after the force is stopped, the hydrogen bonds recombine within seconds, giving the material strong anti-sagging properties and effectively resisting the scouring of the initial water flow.
[0029] Further preferably, to compensate for the weak initial physical framework of the low-viscosity system, this invention introduces chopped reinforcing fibers with a length of 1-3 mm, which can be combined with microsilica to form a physical reinforcement system. The chopped reinforcing fibers form an overlapping support network inside the material, which helps to improve the material's anti-sagging ability and overall stability after curing. The chopped reinforcing fibers are one of chopped basalt fibers, alkali-resistant glass fibers, or carbon fibers, with chopped basalt fibers being preferred. Microsilica can play a micro-filling role, increasing the density of the inorganic phase and improving the resistance of the repair material to chloride ion intrusion.
[0030] The core innovation of this invention lies in the design and implementation of a "step-by-step curing" mechanism. This mechanism relies on the synergistic control of long-chain alkylsilanes (such as hexadecyltrimethoxysilane or octadecyltriethoxysilane) and delayed crosslinking agents (such as tetraethyl orthosilicate, methyltriethoxysilane, or phenyltrimethoxysilane). During the preparation and extrusion stage (self-anchoring period): relying on high-speed shear force, the long hydrophobic carbon chains of long-chain alkylsilanes (HDTMS is preferred) are in situ coated on the surface of polar sulfoaluminate cement particles, forming a layer of "hydrophobic microcapsules," which blocks the early hydration of cement and ensures sufficient operation and spreading time for the material underwater. At the same time, the delayed crosslinking agent (TEOS is preferred) hardly reacts before contact with a large amount of water due to its large steric hindrance, ensuring that the initial cohesion of the matrix is extremely low, allowing the polyphenolic hydroxyl groups of tannic acid (TA) to be released to the interface without hindrance and chelate with calcium ions on the concrete surface, completing the first stage of rapid underwater self-anchoring.
[0031] During the underwater service phase (sequential curing period): As interfacial water and ambient water gradually penetrate into the material, the second stage of curing begins. The penetrating water molecules first trigger a slow de-alcoholization crosslinking reaction between the delayed crosslinking agent (TEOS is preferred) and the terminal hydroxyl groups of 107 colloid, forming an elastic organic waterproof crosslinking network on the material surface. Subsequently, as water further penetrates the hydrophobic microcapsule membrane of the long-chain alkylsilane (HDTMS is preferred), the third stage of curing begins. The internal sulfoaluminate cement begins a hydration reaction, generating a large number of needle-like ettringite crystals. These rigid inorganic hydration products interweave and grow between the flexible de-alcoholized silica gel network and basalt fibers, ultimately completing the sequential formation and shaping of the organic-inorganic interpenetrating network structure from the outside to the inside.
[0032] Preferably, the silane coupling agent is a compound containing amino silanes (such as KH-792) and epoxy silanes (such as KH-560). The active epoxy groups of KH-560 can not only bond with the hydroxyl groups on the concrete surface in the underwater environment, but also undergo ring-opening crosslinking with the amino groups of KH-792 and the phenolic hydroxyl groups of tannic acid, resulting in a dense interaction between the concrete substrate and the repair material, thereby increasing the underwater bond strength to over 2.5 MPa.
[0033] This invention also provides a method for preparing the above-mentioned organic-inorganic hybrid repair material. In order to prevent explosive polymerization in the reactor, strict temperature control and feeding sequence are required, and the method specifically includes the following steps: Step 1: Pre-melt and stir the hydroxyl-terminated polydimethylsiloxane, hydrophobic tackifying resin, polyamide wax from the thixotropic agent, and chopped reinforcing fibers at 110-120℃ for 15-30 minutes. In this step, the high temperature not only completely melts the hydrophobic tackifying resin, but more importantly, the low viscosity and stirring shear force fully disaggregate and disperse the basalt fibers, preventing them from entangled later.
[0034] Step 2: Add the inorganic powder filler in batches. If the thixotropic agent contains hydrophobic fumed silica, add the hydrophobic fumed silica simultaneously in this step. Initiate dehydration at 110-120°C under vacuum at 0.09-0.1 MPa for 40-60 minutes. This step physically removes free water from the powder surface and pores. The temperature must then be lowered to below 40°C; otherwise, premature reaction of the crosslinking agent may easily occur.
[0035] Step 3: After removing the vacuum and introducing nitrogen protection, liquid butyl rubber and pre-dried sulfoaluminate cement are added sequentially in a low-temperature environment below 40°C. Subsequently, a mixture of long-chain alkylsilane, a delayed crosslinking agent, a silane coupling agent, and a catalyst is slowly added dropwise. At this point, a high-speed shearing mode of 8000-12000 rpm is applied. This step is crucial for the "hydrophobic microcapsule" encapsulation; the high shear promotes the uniform dispersion of long-chain alkylsilane on the surface of sulfoaluminate cement particles, forming a hydrophobic coating layer. Dibutyltin dilaurate acts as an organotin catalyst, catalyzing the subsequent hydrolysis and condensation of alkoxysilanes under water-involved conditions and their crosslinking reaction with terminal hydroxyl polydimethylsiloxane. Due to the dehydration treatment and temperature control in the early stages, the crosslinking reaction during preparation and storage is inhibited.
[0036] Step 4: After confirming that the temperature inside the reactor has dropped to 35℃ or room temperature, add pre-dehydrated tannic acid under nitrogen protection, and switch to low-speed tumbling and stirring to remove bubbles for 10-20 minutes. This step is carried out at low temperature and in an oxygen-free environment to maximize the protection of the activity of the biomimetic self-anchoring groups. Finally, degas under vacuum and directly extrude and encapsulate.
[0037] The scanning electron microscope (SEM) image of the organic-inorganic hybrid repair material obtained by the above preparation method is shown below. Figure 1 and Figure 2 As shown: Having a continuous flexible organic substrate (such as Figure 1 (Dark areas in the image): The wavy, continuous, and dense dark matrix in the image is an organic waterproof network formed by hydroxyl-terminated polydimethylsiloxane (107 glue), liquid butyl rubber (PIB), and de-alcoholization crosslinking with a delayed crosslinking agent (preferably TEOS). This flexible network provides excellent hydrophobic film-draining ability and thixotropic anti-sagging properties in the early and middle stages of curing.
[0038] Having a rigid inorganic hydration framework (such as Figure 2 (Bright particles in the image): The bright particles of various shapes scattered throughout the image represent sulfoaluminate cement particles, nano-calcium carbonate, and microsilica. Some nearly spherical particles and crystalline particles with sharp edges can be seen. These inorganic phases are not outside the system but are firmly locked in by the organic phase.
[0039] Achieving microscopic encapsulation and slow-release hydration: The interface between the particles and the organic matrix is extremely smooth and tight, with no obvious macroscopic pores or phase separation. This directly confirms the in-situ encapsulation effect of long-chain alkylsilanes (preferably HDTMS) on cement particles under high-speed shear. This encapsulation delays early hydration, avoids the defect of flash solidification of inorganic phases in water-rich environments, and ensures that later hydration products (such as ettringite and CSH gel) can slowly interpenetrate and grow in the soft organic matrix, eventually completing the ordered structure.
[0040] The sources of the main raw materials used in the following examples: Hydroxyl-terminated polydimethylsiloxane (107 adhesive): Zhejiang Xin'an Chemical Co., Ltd., with viscosities of 4000 mPa·s, 5000 mPa·s, and 6000 mPa·s; the high-viscosity control sample was 50000 mPa·s.
[0041] Hydrophobic tackifying resins: Arakawa Chemical, hydrogenated rosin glycerol ester (softening point 85℃); hydrogenated rosin pentaerythritol ester (softening point 105℃).
[0042] Thixotropic agents: polyamide wax, Elementis Thixatrol ST; hydrophobic fumed silica, Evonik AEROSIL R972.
[0043] Inorganic powder fillers: Nano-calcium carbonate, Shanghai McLean Biochemical Technology Co., Ltd.; Microsilica powder, Wuxi Yiwente New Materials Co., Ltd.
[0044] Liquid butyl rubber (PIB): BASF, Oppanol B15.
[0045] Sulfoaluminate cement (SAC): Tangshan Jidong Cement, rapid-hardening sulfoaluminate cement, grade 42.5 and grade 52.5.
[0046] Long-chain alkylsilanes: Dow Corning, hexadecyltrimethoxysilane (HDTMS).
[0047] Delayed crosslinking agent: Evonik, tetraethyl orthosilicate (TEOS).
[0048] Silane coupling agents: Nanjing Shuguang Chemical, KH-792 (diamino), KH-560 (epoxy).
[0049] Catalyst: Aladdin reagent, dibutyltin dilaurate (DBTDL).
[0050] Tannic acid (TA): Aladdin reagent, purity ≥99%.
[0051] Short-cut reinforcing fiber: Shijiazhuang Basalt Fiber Company, 2mm in length; Alkali-resistant glass fiber, 3mm in length.
[0052] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0053] Example 1 The underwater self-anchoring and stepped curing organic-inorganic hybrid repair material of this embodiment comprises the following components by mass parts: 100 parts of 107 glue (hydroxyl-terminated polydimethylsiloxane, viscosity 5000 mPa·s), 10 parts of hydrogenated rosin glycerol ester, 2 parts of polyamide wax, 1 part of hydrophobic fumed silica (R972), 18 parts of nano calcium carbonate, 7 parts of micro silica powder, 20 parts of liquid butyl rubber (PIB), 20 parts of 42.5 grade sulfoaluminate cement (pre-dried to constant weight at 110℃), 3 parts of hexadecyltrimethoxysilane (HDTMS), 2 parts of tetraethyl orthosilicate (TEOS), 1 part of KH-792, 1 part of KH-560, 0.1 part of dibutyltin dilaurate (DBTDL), 3 parts of tannic acid (dehydrated in a vacuum drying oven at room temperature for 24 hours), and 2 parts of short-cut basalt fiber (2 mm in length).
[0054] The preparation method of the above-mentioned organic-inorganic hybrid remediation material includes the following steps: Step 1 (High-Temperature Co-melting and Fiber Dispersion): Accurately weigh 100g of 5000mPa·s 107 resin and add it to a planetary stirred tank equipped with a jacketed temperature control and vacuum system. Then add 10g of flake hydrogenated rosin glycerol ester, 2g of polyamide wax powder, and 2g of chopped basalt fibers. Seal the reactor, turn on the heat transfer oil to heat to 115℃, and simultaneously turn on the dual planetary paddles to stir and activate at 300rpm for 25 minutes.
[0055] Status observation: At this stage, hydrogenated rosin glycerol ester is completely melted, and polyamide wax swells and is activated in the silica substrate; thanks to the low viscosity system matrix at high temperature, basalt fibers are disintegrated by strong shear force, and the system presents a uniform translucent amber-colored filamentous fluid without any fiber clumping.
[0056] Step 2 (Physical Dehydration): Maintain the reactor temperature at 115℃, and slowly add the mixture of nano-calcium carbonate and micro-silica powder (inorganic powder filler) in two batches (10g first, 15g second), along with 1g of hydrophobic fumed silica. Seal the reactor, turn on the high vacuum pump to achieve a vacuum level of -0.095MPa, and continue high-temperature vacuum dehydration for 50 minutes.
[0057] Status observation: Water mist can be observed to precipitate on the sight glass and be drawn away, and free water in the pores of the powder is completely removed. Then, heating is stopped, and -5℃ coolant is introduced into the jacket to rapidly cool the material in the reactor to 38℃ within 20 minutes.
[0058] Step 3 (Inorganic Phase Microcapsule Encapsulation): Remove the vacuum and purge with high-purity nitrogen for protection. Add 20g of liquid butyl rubber and 20g of pre-dried sulfoaluminate cement sequentially at 38℃. Mix 3g HDTMS, 2g TEOS, 1g KH-792, 1g KH-560, and 0.1g DBTDL thoroughly beforehand, then slowly add the mixture dropwise into the reactor over 5 minutes using a dropping funnel. Switch to high-speed shear dispersion mode, adjust the main impeller speed to 10000rpm, and perform strong shearing for 20 minutes while maintaining cooling to ensure the maximum temperature does not exceed 42℃.
[0059] State observation: The system transforms into a fine, viscous, dark gray paste. Under this strong shear, the long-chain HDTMS rapidly forms a film encapsulating the cement particles, while the remaining crosslinking agents remain uniformly latent.
[0060] Step 4 (Self-anchoring group implantation): After confirming that the system temperature has dropped to 35°C, add 3g of tannic acid that has been dehydrated in a room temperature vacuum drying oven for 24 hours under nitrogen protection, and stir at a low speed of 150rpm for 15 minutes to mix it evenly; then stop the nitrogen supply, turn on the vacuum system again to degas, and after breaking the vacuum, use a hydraulic discharge machine to squeeze it into a light-proof aluminum-plastic tube and seal it.
[0061] The resulting product underwent performance testing, and the results are as follows: The material prepared in this embodiment was smoothly extruded underwater, resembling a thick honey. Upon contact with the underwater concrete substrate, the initial underwater contact angle was measured to be only 15°, demonstrating strong drainage and dispersion capabilities. After being applied to a vertical interface, the polyamide wax and fiber network instantly recombined, achieving a vertical anti-sagging height of 250mm, completely resisting the scouring of a 0.5m / s water flow. The initial underwater setting (self-anchoring) time was 3 minutes, at which point the material was firmly anchored to the interface by tannic acid. After 28 days of curing, deep de-alcoholization and cement hydration were completed, resulting in an underwater shear bond strength of 3.2MPa. The failure mode of the test block was cohesive failure within the concrete matrix (i.e., the colloid did not detach, but the cement matrix was torn), and the compressive strength retention rate reached 95%.
[0062] Example 2 The formulation in this embodiment aims to further reduce the initial viscosity of the system to improve permeability. The difference from Example 1 is that: hydrogenated rosin glycerol ester is reduced to 5 parts, the thixotropic agent is only 1 part polyamide wax (without hydrophobic fumed silica), nano-calcium carbonate is reduced to 10 parts, microsilica powder is reduced to 5 parts, and chopped basalt fiber is reduced to 1 part. Other components and preparation methods (temperature and time control at each stage) are exactly the same as in Example 1.
[0063] Product status: In steps 1 and 2, due to the significant reduction in solid filler, the system exhibits extremely high fluidity. The resulting product has a semi-flowing, stringy gel-like appearance.
[0064] Performance Testing: During underwater extrusion, the material can be smoothly extruded under an extrusion thrust of approximately 20 N and penetrates underwater concrete microcracks with a width of approximately 0.5 mm under the coating action. The initial underwater contact angle is as low as 12°; due to the weakening of the thixotropic system, the vertical sag resistance is reduced to 120 mm (not suitable for thick coating on large-area vertical surfaces, but suitable for crack filling); the combination of tannic acid and low-viscosity substrate results in an initial underwater setting time of 4 minutes; the 28-day underwater shear bond strength is 2.6 MPa.
[0065] This embodiment demonstrates that by reducing the amount of solid filler, thixotropic agent, and chopped reinforcing fiber, the underwater wetting and microcrack penetration capabilities of the material can be further improved; correspondingly, its resistance to sag on the facade is reduced. Therefore, it is more suitable for underwater microcrack grouting than for large-area thick-coat repair of facades.
[0066] Example 3 The formulation in this embodiment is designed to withstand extremely harsh dynamic water scouring environments. The difference from Example 1 is that: hydrogenated rosin glycerol ester is increased to 15 parts, polyamide wax to 3 parts, hydrophobic fumed silica (R972) to 2 parts, nano-calcium carbonate to 20 parts, microsilica powder to 10 parts, liquid butyl rubber and sulfoaluminate cement both to 30 parts, crosslinking agent TEOS to 4 parts, and basalt fiber to 4 parts. In the preparation method, the high-speed shearing time in step 3 is extended to 30 minutes to ensure sufficient dispersion of the high solids content. Other components and preparation methods are the same as in Example 1.
[0067] Product state: The finished product is a highly dense, strong-boned clay-like substance.
[0068] Performance testing: The required extrusion thrust during underwater extrusion was approximately 80 N, indicating that the extrusion resistance of the material was significantly increased compared to Example 2 due to the increased dosage of thixotropic agent, inorganic phase, and chopped reinforcing fibers. However, after the material contacted the substrate and was subjected to smear shearing, it could still effectively displace the interfacial water film, with an initial underwater contact angle of 22°. After the external force was removed, the material rheology showed that the vertical anti-sagging height increased to 350 mm, and there was no flow deformation under the simulated strong ocean current of 1.5 m / s. The initial underwater setting time was approximately 5 minutes. Due to the increase of TEOS and inorganic phase, the rigid skeleton formed by the subsequent stepwise solidification was robust, and the underwater shear bond strength reached 3.5 MPa after 28 days.
[0069] This embodiment demonstrates that by increasing the amounts of hydrophobic tackifier, thixotropic agent, inorganic phase, and chopped reinforcing fiber, the material's resistance to sag and erosion by flowing water can be significantly enhanced. Simultaneously, due to the increased solids content and cohesive effect of the system, the underwater interface spreading ability is reduced compared to the low-solids content formulation. Therefore, this formulation is more suitable for facade or thick-layer repair under strong flowing water conditions.
[0070] Example 4 The organic-inorganic hybrid repair material of this embodiment differs from that of Example 1 in that: 10 parts of the hydrophobic tackifying resin are replaced by an equal amount of hydrogenated rosin glycerol ester (softening point 85°C) with hydrogenated rosin pentaerythritol ester (softening point 105°C); and 2 parts of short-cut basalt fiber (2 mm in length) are replaced with alkali-resistant glass fiber (3 mm in length). Other components are the same as in Example 1.
[0071] Preparation process and conditions: In the high-temperature eutectic stage of step 1, due to the high softening point of pentaerythritol ester, the activation temperature in the reactor was slightly increased to 120°C to ensure complete melting. The alkali-resistant glass fibers showed good dispersibility and no agglomeration was observed. Other preparation methods were the same as in Example 1.
[0072] Performance Testing and Results: The use of hydrogenated pentaerythritol rosin resulted in a slightly dry initial tackiness after extrusion, but it still effectively dissipated water film under coating shear force, with an initial underwater contact angle of 16°. The introduction of alkali-resistant glass fiber made the thixotropic skeleton of the material more robust, achieving a vertical anti-sagging height of 230mm. The initial underwater setting time was approximately 4 minutes. After curing, due to the extremely high modulus of the alkali-resistant glass fiber, the overall rigidity of the repair layer was improved, and its resistance to deformation was enhanced. After 28 days of curing, the underwater shear bond strength reached 3.1MPa. This provides an effective means of adjusting the curing rhythm for construction in different water temperatures (such as low-temperature waters in winter).
[0073] Example 5 The components and preparation method of this embodiment are the same as those of Example 1, except that 2 parts of the delayed crosslinking agent tetraethyl orthosilicate (TEOS) are replaced with 2 parts of methyltriethoxysilane (MTES).
[0074] Preparation process and status: Since the molecular steric hindrance of MTES is slightly smaller than that of TEOS, during the in-reactor preparation process in steps 3 and 4, due to strict temperature control (<42℃) and high vacuum dehydration, premature cross-linking was not triggered, and the material was discharged safely and smoothly.
[0075] Performance test results: In underwater applications, the time required for the formation of an elastic waterproof barrier membrane on the material surface is used to characterize the surface cross-linking film formation process. In this embodiment using MTES, the time is approximately 1 hour, while in Example 1 using TEOS, it is approximately 2 hours, representing a reduction of about 50% in surface film formation time. After extrusion, the material can smoothly adhere to a wet substrate, with an initial underwater contact angle of 15°, a vertical anti-sagging height of 250 mm, an underwater self-anchoring time of 3 minutes, and a final 28-day underwater shear bond strength of 3.0 MPa.
[0076] Example 6 This embodiment aims to improve later-stage strength and interfacial covalent bonding. The difference from Example 1 is that the 42.5 grade sulfoaluminate cement is replaced with the higher-strength 52.5 grade sulfoaluminate cement; both parts of the silane coupling agent are KH-560 containing active epoxy groups, and the aminosilane KH-792 is removed. Other components and preparation methods are the same as in Example 1.
[0077] Preparation process and state: After removing the catalytically active amino group, the in-reactor preparation system becomes more stable and the operating window is greatly widened.
[0078] Performance Testing and Results: Underwater application was smooth, and initial physical drainage and tannic acid anchoring started normally (contact angle 15°, anti-sagging 260mm, initial setting 4 minutes). During the sequential curing stage, the ettringite generated by the hydration of 52.5 grade cement had a higher density; simultaneously, two parts of pure KH-560 formed dense ring-opening crosslinks with the hydrated calcium silicate (CSH) and tannic acid phenolic hydroxyl groups at the concrete interface. After 28 days of curing, the test blocks exhibited extremely deep cohesive failure within the concrete, with the underwater shear bond strength rising to 3.4 MPa and the compressive strength retention rate reaching as high as 97%.
[0079] Example 7 This embodiment explores a low-viscosity substrate by replacing hydroxyl-terminated polydimethylsiloxane with 4000 mPa·s; other components and preparation are the same as in Example 1.
[0080] Performance Testing and Results: The material exhibits superior fluidity, rapidly displacing the water film underwater and instantly filling uneven surfaces on the substrate, reducing the initial underwater contact angle to 14°. The synergy between the polyamide wax and fibers still maintains a vertical anti-sagging height of 210mm, fully meeting construction requirements. Underwater initial setting time is 3 minutes, and underwater shear bond strength is 3.1MPa.
[0081] Example 8 The components and preparation of this embodiment are the same as in Example 1, except that the hydroxyl-terminated polydimethylsiloxane is replaced with a viscosity of 6000 mPa·s.
[0082] Performance Testing and Results: The extrusion resistance of the material increased slightly, but it is still an easily spreadable paste. The internal polymer chain entanglement increased, the initial cohesive force was slightly greater, the underwater drainage time increased by about 1-2 seconds, and the initial underwater contact angle increased slightly to 18°; its advantage lies in its stronger ability to resist the initial impact of strong water flow, with a vertical anti-sag height of 280mm; the underwater shear bond strength is 3.0MPa.
[0083] Example 9 The components and preparation of this embodiment are the same as in Example 1, except that the amount of tannic acid is increased by 4 parts.
[0084] Performance Testing and Results: The material undergoes adsorption upon underwater extrusion coating, reducing the underwater initial setting (self-anchoring) time to a minimum of 2 minutes. With increasing tannic acid content, the probability of it capturing calcium ions at the interface increases, achieving penetrating anchoring even on uncleaned concrete surfaces containing a small amount of microalgae, with a 28-day underwater shear bond strength of 3.3 MPa.
[0085] Example 10 The composition and preparation of this embodiment are the same as those of Example 1, except that: all 25 parts of the inorganic powder filler are made of nano-calcium carbonate, and microsilica powder is removed.
[0086] Performance testing and results: The material rheology was normal, and the interface anchoring was unaffected (contact angle 16°, anti-sagging 240mm, initial setting 3 minutes). However, after long-term curing, due to the lack of microsilica pozzolanic reaction to fill the tiny capillary pores after cement hydration, the density of the repair layer decreased slightly; this was manifested in the chloride ion diffusion coefficient reduction rate dropping from 82% in Example 1 to 73%, the compressive strength retention rate decreasing to 90%, and the underwater shear bond strength at 2.9MPa, but still meeting most conventional freshwater underwater repair specifications.
[0087] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
[0088] Comparative Example 1 This comparative example aims to illustrate the necessity of reducing initial cohesion.
[0089] The only difference between this example and Example 1 in terms of components and preparation method is that the 5000 mPa·s 107 adhesive substrate is directly replaced with a commercially available 50000 mPa·s high-viscosity 107 adhesive. Everything else is the same as in Example 1.
[0090] Preparation status: During preparation in the reactor, the high viscosity of the base adhesive resulted in extremely high stirring resistance, and the basalt fibers exhibited partial clumping.
[0091] Performance Testing: When the material was squeezed into water and pressed onto a concrete pier, due to the extremely high long-chain entanglement cohesion of the 50,000 mPa·s butyl rubber, the material behaved like a highly resilient, hard putty. Under pressure, the elastic recoil force (cohesion) within the material was far greater than the wetting force of the liquid butyl rubber attempting to displace the water film; the initial underwater contact angle reached as high as 65°, and the material was completely unable to wet the micropores of the substrate. As soon as the pressure was released, the water film immediately re-entered the interface, and the entire piece of material slid off. Underwater initial setting (self-anchoring) failed, and the underwater bond strength was only measured at 0.4 MPa.
[0092] This comparative example illustrates the decisive role of ultra-low viscosity rheological chassis in underwater forced drainage.
[0093] Comparative Example 2 This comparative example aims to illustrate the decisive role of a highly effective hydrophobic thickening phase in forcibly displacing the interfacial water film and maintaining the initial structural integrity during extrusion.
[0094] The only difference between this formulation and Example 1 in terms of components and preparation method is that hydrogenated rosin glycerol ester and liquid butyl rubber (PIB) have been completely removed from the formulation. Everything else is the same as in Example 1.
[0095] Preparation and product states: During the in-reactor preparation stage, due to the removal of high-viscosity resin and rubber, the system is left with only 5000 mPa·s of low-viscosity 107 glue encapsulating a large amount of inorganic powder. The discharged state is a loose paste lacking stringiness and cohesive viscosity.
[0096] Performance testing: The material undergoes phase separation before contacting the substrate, exhibiting dispersion upon contact with water, being washed away by the water flow, and turning into turbid flocculent suspensions mixed into the water. The material is unable to form on the substrate surface at all; the initial underwater contact angle cannot be determined; and the vertical anti-sag height is 0 mm. Underwater initial setting (self-anchoring) failed; due to the inability to form, the underwater shear bond strength is recorded as 0 MPa.
[0097] This comparative example verifies that in ultra-low viscosity substrate systems, the highly effective hydrophobic thickening phase acts as a physical barrier to prevent the material from dispersing or dissolving in a water-rich environment.
[0098] Comparative Example 3 This comparative example aims to illustrate the necessity of tannic acid polyphenol hydroxyl chelation for achieving underwater chemical self-anchoring.
[0099] The only difference between the components and preparation method and Example 1 is that tannic acid (TA), which provides biomimetic adhesion in the formulation, is removed.
[0100] Preparation and product states: During in-reactor preparation, the rheological properties of the system were not significantly affected, and the discharged state was a normal stringy thixotropic paste.
[0101] Performance Testing: When this material was extruded into water and applied to concrete piers, although the low-viscosity substrate and hydrophobic thickening phase successfully displaced the macroscopic water film at the interface (the initial contact angle remained at 18°), the lack of tannic acid polyphenol hydroxyl groups to actively capture and chelate free calcium ions (Ca) on the concrete surface hindered its performance. 2+The material could only "virtually adhere" to the substrate using weak intermolecular van der Waals forces. When subjected to simulated 0.5 m / s water flow, the interfaces, now free from covalent and coordination bonds, were easily re-invaded and replaced by water molecules. Within 20 minutes of application, irreversible warping and peeling occurred at the edges of the repair layer. Underwater initial setting (self-anchoring) was deemed a failure, and after 28 days, the underwater bond strength decreased to only 1.1 MPa.
[0102] This comparative example demonstrates the decisive role of tannic acid biomimetic groups in transcending simple physical wetting and constructing a robust underwater chemical anchoring interface.
[0103] Comparative Example 4 This comparative example aims to illustrate the core role of long-chain alkylsilanes (HDTMS) in constructing "hydrophobic microcapsules" in delaying inorganic hydration in a stepwise solidification mechanism.
[0104] The difference between this example and Example 1 in terms of components and preparation method is that HDTMS is not added to the formulation. Everything else is the same as in Example 1.
[0105] State and Performance Testing: The in-reactor preparation process proceeded relatively smoothly, with successful material discharge. However, it performed poorly in underwater applications: upon extrusion into a water-rich environment, water molecules instantly penetrated without any hydrophobic barrier, directly contacting the highly active, rapid-hardening sulfoaluminate cement particles. Within a mere 45 seconds of extrusion, the cement flash-set, releasing significant heat and instantly transforming the previously soft, stringy colloid into a dry, hardened powder, completely losing its thixotropic coating properties. This indicates that the hierarchical structure (first organic surface cross-linking for waterproofing, then slow inorganic hydration internally) was completely disrupted. The cured material exhibited numerous microcracks and unexpelled air bubbles due to excessively rapid hydration, resulting in an extremely porous structure. The underwater shear bond strength was only 1.4 MPa, and the chloride ion diffusion coefficient reduction rate was only 35%, indicating a lack of waterproofing and corrosion resistance.
[0106] Comparative Example 5 This comparative example aims to illustrate the significance of using a delayed crosslinking agent (TEOS) instead of the deoxime crosslinking agent commonly used in conventional silicone sealants.
[0107] The difference in components and preparation method compared to Example 1 is that 2 parts of the slow-release TEOS are replaced with 2 parts of a conventional, highly active deoxime-type crosslinking agent: methyltributanone oxime silane (MOS). Everything else is the same as in Example 1.
[0108] Preparation status and process record: Steps 1 and 2, involving high-temperature slurry preparation and dehydration, proceeded normally. However, during step 3 (at an internal temperature of 38°C), when MOS was mixed with KH-792 coupling agent containing diamino groups and added dropwise into the reactor, the amino groups exhibited an extremely strong catalytic effect on the MOS. Since it is extremely difficult to achieve 100% absolute anhydrousness in inorganic powders, trace amounts of bound water remained in the pores. The equipment shut down due to overload protection only after the third minute of high-speed shearing.
[0109] Test results: Upon opening the observation port, it was found that explosive polymerization had occurred inside the reactor, making it impossible to discharge material or add tannic acid. This comparative example demonstrates that in complex hybrid systems rich in polar inorganic fillers and amino additives, introducing conventional highly active crosslinking agents is completely infeasible; process safety must be ensured by relying on the slow-moving properties of molecules with large steric hindrance, such as TEOS.
[0110] Comparative Example 6 This comparative example aims to illustrate the indispensability of fiber lap networks in ultra-low viscosity substrates.
[0111] The composition and preparation method differ from Example 1 in that short-cut basalt fibers are not added. Everything else is the same as in Example 1.
[0112] Preparation status and performance testing: The material discharged from the autoclave was extremely smooth. However, in underwater applications, it lost its physical support. While the material could adhere to the substrate and displace the water film (contact angle 15°, initial setting 3.5 minutes), when the coating thickness on vertical piers exceeded 3mm, the material's own weight exceeded its internal thixotropic yield value, resulting in large-area severe sagging and flow, reducing the vertical anti-sagging height to 40mm. After curing, lacking fiber toughening, it fractured brittlely under slight mechanical impact underwater, failing to meet engineering requirements.
[0113] Comparative Example 7 The components and preparation method of this comparative example differ from those of Example 1 in that the amount of the delayed crosslinking agent TEOS is increased to 8 parts.
[0114] Performance Testing: Initial underwater construction performance was normal. However, during the curing stage, excessive TEOS led to abnormally high de-alcoholization crosslinking density due to moisture infiltration. This dense organic three-dimensional network not only caused the matrix to harden and become brittle but also generated crosslinking shrinkage stress. When the internal sulfoaluminate cement subsequently underwent hydration and expansion, the brittle outer organic network could not adapt to this micro-expansion. On the 7th day of underwater curing, numerous micro-cracks visible to the naked eye appeared on the surface of the repair layer. Moisture entered the failure interface, and the underwater shear bond strength dropped to 1.8 MPa after 28 days.
[0115] Comparative Example 8 The difference between the components and preparation method of this comparative example and Example 1 is that polyamide wax and hydrophobic fumed silica R972 are not added.
[0116] Product Status and Performance Testing: The material exhibits a completely low-viscosity, flowing liquid state, losing its intelligent rheological properties. During underwater extrusion, the material exhibits significant flow, failing to maintain the specified coating thickness, with a vertical anti-sagging height of 0 mm. Under a 0.5 m / s water flow, most of the material is dispersed, with only a small amount remaining on the substrate surface. The 28-day underwater shear bond strength is only 0.5 MPa.
[0117] Comparative Example 9 The components of this comparative example are exactly the same as those of Example 1, except for the different preparation process: the short-cut basalt fibers are not added during the high-temperature eutectic period in step 1, but are added together with cement at 38°C in step 3.
[0118] Preparation status: In the paste at 38℃, due to the high filler density and thixotropic structure of the system, the fibers not only did not disintegrate under high-speed shearing, but instead became entangled and formed severe agglomerates; clogging of the glue gun nozzle during extrusion.
[0119] Performance testing: After being applied to the concrete surface, numerous unwetted fiber clusters remained inside, becoming stress concentration points. The material's mechanical properties decreased, with an underwater shear bond strength of only 1.6 MPa.
[0120] Comparative Example 10 The components of this comparative example are exactly the same as those in Example 1. The difference lies in the preparation process: the high-temperature vacuum dehydration time in step 2 is shortened from 50 minutes to 15 minutes.
[0121] Product storage condition: Due to the incomplete removal of bound water from the deep pores of the inorganic filler (especially nano-calcium carbonate), when cooled to 38°C and TEOS and catalyst were added, this residual internal water began to slowly initiate cross-linking after being sealed into the tube. In this comparative example, after only 3 days in a room-temperature warehouse (the normal shelf life of materials is more than 6 months), the tip of the tubing hardened into stone, rendering the entire tube unusable and losing its engineering practical value.
[0122] Comparative Example 11 The components of this comparative example are exactly the same as those in Example 1. The difference lies in the preparation process: the tannic acid was not dehydrated at room temperature, but was directly baked in a high-temperature oven at 110°C, and was added during the high-temperature period of 115°C in step 1.
[0123] Product Status and Performance Testing: The pyrogallol structure of tannic acid was completely oxidized and decomposed under high temperature and aerobic conditions, turning the originally yellowish-brown powder into charred waste. After being extruded underwater, the material completely lost its ability to capture and chelate calcium ions; its interfacial adhesion performance in dynamic water environments was the same as that of Comparative Example 3 (without tannic acid), and it was easily overturned and peeled off by water flow after application, resulting in failure of underwater self-anchoring. The final underwater shear bond strength was approximately 1.2 MPa.
[0124] Comparative Example 12 The difference between the components and preparation method of this comparative example and Example 1 is that the amount of sulfoaluminate cement is reduced to 5 parts.
[0125] Product Status and Performance Testing: In the final stage of the phased curing process, due to insufficient inorganic hydrated phase, the resulting rigid ettringite crystals are sparse and unable to support a coherent load-bearing framework within the soft polysiloxane substrate. After 28 days of curing, the repair material exhibits extremely low hardness and is highly susceptible to permanent creep under pressure. The underwater compressive strength retention rate plummets to 52%, and the underwater shear bond strength is only 1.5 MPa, insufficient to withstand the stress deformation of marine structures.
[0126] Comparative Example 13 The difference between the components and preparation method of this comparative example and Example 1 is that KH-792 and KH-560, which have active functional groups, are completely replaced with conventional inert coupling agents: methyltrimethoxysilane (MTMS).
[0127] Product Status and Performance Testing: MTMS can only barely improve the dispersion of powder in the organic phase, but due to the lack of amino and epoxy groups, it completely loses the ability to form covalent bonds between the matrix, inorganic filler, and concrete surface. Initial adhesion is acceptable, but after 28 days of underwater curing, the underwater shear bond strength is 1.5 MPa, significantly lower than that of Example 1; its chloride ion diffusion coefficient also decreased to 70%, indicating that the long-term interfacial stability decreases due to the lack of amino and epoxy active functional groups.
[0128] Comparative Example 14 This comparative example violates the design principle of forced drainage at the interface, involving components and preparation methods. The difference from Example 1 is that hydrogenated rosin glycerol ester and liquid butyl rubber are completely replaced with dimethyl silicone oil. Everything else is the same as in Example 1.
[0129] Product Status and Performance Testing: Dimethyl silicone oil not only lacks the high polar repulsion force to force water molecules to repel, but also makes the material greasy and non-stick to the substrate. When extruded underwater, the material is incompatible with the water film but cannot penetrate it, and it slides off easily with a light touch. The initial contact angle is as high as 58°, indicating that the material's ability to repel the interfacial water film and spread and wet is significantly reduced, making interfacial slippage easy to occur during construction. Although the material can gradually cure afterward, with a self-anchoring time of about 3 minutes, the 28-day underwater shear bond strength is only 1.4 MPa, significantly lower than that of Example 1.
[0130] Comparative Example 15 The components of this comparative example are exactly the same as those in Example 1. The difference lies in the change of the preparation method: the high-speed shearing speed in step 3, the coating stage, is reduced from 10,000 rpm to a low-shear condition of 1,500 rpm.
[0131] Product Status and Performance Testing: The extremely low shear force was insufficient to provide enough mechanical force for the long-chain alkylsilane (HDTMS) to spread and coat the surface of cement particles evenly. This resulted in a chaotic state within the material, with both uncoated and multi-layered cement particles coexisting. After extrusion into water, the uncoated cement rapidly flash-set locally within 30 seconds, producing a large number of hard particles (dead spots); while the over-coated cement could not come into contact with water for several months to hydrate. The stress within the entire repair layer was extremely uneven, with numerous unhydrated defects, resulting in extremely poor and unstable mechanical performance. The bond strength of the five tested groups varied greatly, with an average of only 1.6 MPa. This comparative example demonstrates the decisive role of the high-shear coating process.
[0132] Experimental Example The performance testing methods for the above embodiments and comparative examples are explained as follows: (1) Initial underwater contact angle: The material was extruded onto the surface of a smooth concrete specimen in a 20°C water bath, and the droplet shape was captured within 10 seconds after extrusion using an underwater contact angle measuring instrument.
[0133] (2) Vertical anti-sagging height: Refer to GB / T 13477.6 and combine it with underwater construction conditions for testing. Under the action of its own weight and 0.5 m / s simulated water flow, the maximum continuous coating height that the material can maintain without obvious sagging, flowing or falling off within the specified observation time is recorded. This height is taken as the vertical anti-sagging height. The larger the value, the stronger the anti-sagging ability.
[0134] (3) Underwater self-anchoring (initial setting) time: The material is applied underwater to the surface of the test block. The surface is touched lightly with a glass rod every 30 seconds. The underwater self-anchoring time is defined as the time when the material surface shows obvious elastic resistance and does not stick to the glass rod and the interface cannot be easily peeled off.
[0135] (4) Underwater bond strength: In accordance with ASTM C882 standard, two C40 concrete semi-cylindrical specimens were glued on the inclined surfaces and joined together underwater (20±2℃). After underwater curing for 28 days, shear tensile tests were performed using a universal testing machine at a rate of 2mm / min.
[0136] (5) Underwater compressive strength retention rate: The same batch of materials were prepared into underwater curing specimens and control curing specimens, and their compressive strength was measured at the same age. The underwater compressive strength retention rate was calculated according to the following formula: Underwater compressive strength retention rate (%) = compressive strength of underwater curing specimen after 28 days / compressive strength of control curing specimen after 28 days × 100%.
[0137] (6) Chloride ion diffusion coefficient reduction rate: Referring to the chloride ion penetration resistance test method in GB / T 50082—2009, the chloride ion diffusion coefficients of the concrete specimens repaired with the material of this invention and the unrepaired control concrete specimens were determined respectively. The chloride ion diffusion coefficient reduction rate was calculated according to the following formula: Chloride ion diffusion coefficient reduction rate (%) = (chloride ion diffusion coefficient of unrepaired control specimen - chloride ion diffusion coefficient of repaired specimen) / chloride ion diffusion coefficient of unrepaired control specimen × 100%.
[0138] The test results are summarized in Table 1 below: Table 1 Performance test results of the examples and comparative examples
[0139] Note: Comparative Examples 2 and 8 could not be formed due to being dispersed by the water flow, and Comparative Examples 5 and 10 were scrapped due to premature curing inside the reactor or pipe. Therefore, some underwater curing performance could not be tested.
[0140] Table 1 shows that the initial underwater contact angle of the organic-inorganic hybrid repair materials obtained in Examples 1-10 is 12°–22°, the vertical anti-sagging height is 120–350 mm, the underwater self-anchoring time is 2–5 min, and the 28-day underwater shear bond strength is 2.6–3.5 MPa. Different examples can achieve targeted control between interfacial wetting ability and anti-sagging and anti-erosion capabilities by adjusting the amounts of hydrophobic tackifier, thixotropic agent, inorganic powder, and chopped reinforcing fibers. Specifically, in Example 2, reducing the amount of solid filler and thixotropic skeleton reduced the initial underwater contact angle to 12°, exhibiting better microcrack wetting ability, but the vertical anti-sagging height correspondingly decreased to 120 mm. In Example 3, increasing the amounts of thixotropic agent, inorganic phase, and chopped reinforcing fibers increased the vertical anti-sagging height to 350 mm, maintaining morphological stability under simulated 1.5 m / s dynamic water conditions, but the initial underwater contact angle correspondingly increased to 22°. The above results show that the rheological properties of the material of the present invention can be controlled according to different construction requirements such as crack filling repair, thick coating of vertical surfaces and strong dynamic water repair. At the same time, the 28-day underwater shear bond strength of each embodiment is not less than 2.6 MPa.
[0141] In contrast, Comparative Example 1, due to the use of a conventional high-viscosity substrate, had excessive cohesion, resulting in an inability to wet the substrate surface (contact angle 65°), and an underwater bond strength of only 0.4 MPa. Comparative Examples 2 and 14, by removing the hydrophobic tackifier phase or replacing it with dimethyl silicone oil, respectively, both resulted in a significant decrease in interfacial drainage, wetting, and subsequent bonding performance. Comparative Example 8, after removing polyamide wax and hydrophobic fumed silica, essentially lost its anti-sagging ability, indicating that the thixotropic system plays a crucial role in maintaining the underwater construction morphology. Comparative Examples 3 and 11, due to the lack of effective tannic acid or its high-temperature oxidation, completely lost their interfacial chemical anchoring force, and their underwater bond strength dropped to 1.1-1.2 MPa. Comparative Example 4, due to the lack of long-chain silane microcapsule encapsulation, resulted in an underwater bond strength of less than 1 minute. The clock flash condensation and powdering; Comparative Examples 5 and 10 demonstrate that the introduction of conventional high-activity crosslinking agents can cause explosive polymerization in the reactor or incomplete dehydration, which can lead to premature hardening in the tube; Comparative Example 6 shows that the lack of fiber skeleton will cause the anti-sagging performance to collapse (only 40mm); Comparative Examples 9 and 15 reveal that process errors such as incorrect feeding sequence (fiber clumping) or insufficient shear speed (coating failure) can lead to a large number of dead points and stress defects inside the material; Comparative Examples 7, 12, and 13 demonstrate from different dimensions that excessive crosslinking agent leads to network shrinkage and cracking, insufficient inorganic phase leads to the collapse and creep of rigid skeleton, and the selection of coupling agent is wrong and lacks covalent bond protection, all of which will greatly weaken the long-term mechanical and corrosion resistance properties after curing (bonding strength drops to the 1.5-1.8MPa range).
[0142] It is evident that the material formulation of this invention is highly coupled with the "stepwise solidification" preparation process, and neither can be dispensed with, together achieving the excellent performance of the underwater repair material.
Claims
1. An underwater self-anchoring and hierarchical curing organic-inorganic hybrid repair material, characterized in that, It includes the following components by mass parts: The composition includes: 100 parts of hydroxyl-terminated polydimethylsiloxane with a viscosity of 4000-6000 mPa·s, 5-15 parts of hydrophobic tackifying resin, 1-5 parts of thixotropic agent, 15-30 parts of inorganic powder filler, 15-30 parts of liquid butyl rubber, 15-30 parts of sulfoaluminate cement, 2-5 parts of long-chain alkylsilane, 1-4 parts of delayed crosslinking agent, 1-3 parts of silane coupling agent, 0.05-0.15 parts of catalyst, 1-4 parts of tannic acid, and 1-4 parts of short-cut reinforcing fibers with a length of 1-3 mm.
2. The organic-inorganic hybrid repair material according to claim 1, characterized in that, The hydrophobic tackifying resin is one of hydrogenated rosin glycerol ester, hydrogenated rosin pentaerythritol ester, or polymerized rosin; the thixotropic agent is a mixture of polyamide wax and hydrophobic fumed silica in a mass ratio of (1.5~2):1 or is only polyamide wax; the chopped reinforcing fiber is one of chopped basalt fiber, alkali-resistant glass fiber, or carbon fiber.
3. The organic-inorganic hybrid repair material according to claim 1, characterized in that, The inorganic powder filler is a mixture of nano-calcium carbonate and microsilica in a mass ratio of (2~2.57):1, or is only nano-calcium carbonate; the sulfoaluminate cement is grade 42.5 sulfoaluminate cement or grade 52.5 sulfoaluminate cement.
4. The organic-inorganic hybrid repair material according to claim 1, characterized in that, The long-chain alkylsilane is hexadecyltrimethoxysilane or octadecyltriethoxysilane; the delayed crosslinking agent is one of tetraethyl orthosilicate, methyltriethoxysilane or phenyltrimethoxysilane; the silane coupling agent is KH-560, or a mixture of KH-792 and KH-560 in equal proportions; the catalyst is dibutyltin dilaurate.
5. The organic-inorganic hybrid repair material according to any one of claims 1 to 4, characterized in that, The initial underwater contact angle is not greater than 22°, the vertical anti-sag height is not less than 120mm, and the underwater bonding strength is not less than 2.6MPa.
6. The method for preparing the organic-inorganic hybrid repair material according to any one of claims 2 to 5, characterized in that, The following steps are performed in a planetary stirred tank equipped with a jacketed temperature control and vacuum system: Step 1: Pre-melt the hydroxyl-terminated polydimethylsiloxane, hydrophobic tackifying resin, polyamide wax and chopped reinforcing fibers at 110-120℃ and stir to activate for 15-30 minutes; Step 2: Add inorganic powder filler in batches, and add the hydrophobic fumed silica when the thixotropic agent contains hydrophobic fumed silica. Dehydrate under vacuum conditions at 110-120℃ for 40-60 minutes, and then cool down to below 40℃. Step 3: Remove the vacuum and introduce nitrogen protection. Add liquid butyl rubber and pre-dried sulfoaluminate cement at a temperature below 40°C. Then, slowly add a mixture of long-chain alkylsilane, delayed crosslinking agent, silane coupling agent and catalyst. Under high-speed shear, complete the in-situ coating of the cement surface. Step 4: Add pre-dehydrated tannic acid at a temperature below 35°C and under nitrogen protection, stir at low speed until evenly mixed, degas under vacuum, and then seal and package.
7. The preparation method according to claim 6, characterized in that, In step 3, the sulfoaluminate cement is pre-dried to constant weight at 110°C.
8. The preparation method according to claim 6, characterized in that, In step 3, the high-speed shearing speed is 8000-12000 rpm, the shearing time is 15-30 minutes, and the system temperature is controlled to not exceed 45℃.
9. The preparation method according to claim 6, characterized in that, In step 4, the tannic acid needs to be pre-dehydrated in a vacuum drying oven at room temperature for more than 24 hours.
10. The application of the organic-inorganic hybrid repair material according to claim 5 in underwater concrete repair, characterized in that, The application methods include scraping, extrusion, or grouting. The application environment is underwater with a water temperature of 5-35℃. The material is wetted and anchored on the surface of damp or water-rich concrete by its own weight or the pressure of the application.